Perovskite cell based on In (OTf) passivated perovskite layer and preparation method thereof
By using indium trifluoromethylsulfonate passivator in perovskite batteries, the crystallization imbalance and oxidation problems of tin lead perovskite batteries are solved, and efficient and stable perovskite batteries are achieved, which promotes perovskite batteries industrial development.
Patent Information
- Application Number
- CN202411516805.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-17
AI Technical Summary
Mixed tin-lead perovskite solar cells have poor efficiency and stability in crystallization imbalance and spontaneous tin-lead ion oxidation, resulting in limited application of their high-efficiency all-perovskite tandem batteries.
Using indium trifluoromethylsulfonate (In(OTf)) passivator, through its synergistic effect with tin ions in tin lead perovskite, the crystallization process is delayed and tin oxide is preferred, and the narrow band gap perovskite layer is protected to achieve High-quality and stable perovskite battery.
It significantly delays the crystal imbalance of tin lead perovskite, reduces spontaneous oxidation of tin ions, improves the efficiency and stability of the battery, and enhances the photoelectric conversion efficiency and filling factor.
Smart Images

Figure CN119156028A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite cell based on an In(OTf) passivated perovskite layer and a preparation method thereof. Background Art
[0002] Metal halide perovskite solar cells (PSCs) have great prospects in the solar industry due to their excellent optoelectronic properties, light weight and simple structure. Pure lead (Pb)-based PSCs have demonstrated record-breaking power conversion efficiencies (PCEs) of ∼26.7%, comparable to silicon solar cells. However, the band gap of lead-based perovskites is usually over 1.4 eV, resulting in limited photocurrent. In contrast, narrow-bandgap (NBG) (≈1.2 eV) hybrid tin-lead (Sn-Pb) perovskites play a vital role in the development of efficient all-perovskite tandem solar cells. These all-perovskite tandem cells with efficient light harvesting and photon-to-exciton conversion have the potential to surpass the Shockley-Queisser limit of single-junction solar cells and are therefore considered one of the most important pathways for the commercialization of perovskite photovoltaic devices.
[0003] High-quality NBG hybrid Sn-Pb subcells are essential for all-perovskite tandem cells, especially when matched with wide bandgap (WBG) subcells in a tandem configuration for efficient light harvesting. Therefore, it is crucial to utilize high-quality Sn-Pb perovskite films to efficiently collect photons and produce high current density. However, NBG Sn-Pb PSCs suffer from poor efficiency and stability compared to their lead-based counterparts due to rapid crystallization and uneven nucleation. The rapid crystallization of Sn perovskites leads to poor quality Sn-Pb perovskite films, hindering the fabrication of efficient all-perovskite tandem cells and hindering their commercialization.
[0004] Although there are reports on controlling the crystallization of pure Pb or pure Sn perovskites, there are few studies on mixed Sn-Pb perovskites, which face great challenges due to the large solvation difference between Sn and Pb metal ions. 2+ It is easy to oxidize, resulting in high trap density and severe non-radiative recombination. 2+ Existence, Sn 2+ Oxidation can occur at various stages, including before, during and even after the formation of perovskite crystals.
[0005] In view of the crystallization imbalance and spontaneous Sn 2+ Traditional methods of dealing with problems such as oxidation include creating a Sn-rich environment to offset Sn. 2+ Sn vacancies generated by oxidation. For example, adding tin fluoride (SnF 2), used to introduce excess Sn 2+ ions and prevent the formation of unwanted phases. In addition to SnF 2 In addition, Sn powder can be introduced to create a Sn-rich environment and remove the harmful Sn in the perovskite precursor. 4+ Convert to Sn 2+ However, these approaches have limited effectiveness because Sn-Pb perovskite films remain susceptible to oxidation during and after the fabrication process. Intrinsic oxidation can lead to defect diffusion within the perovskite film and low photon-to-exciton conversion efficiency.
[0006] In view of the unbalanced crystallization and spontaneous Sn 2+ Oxidation is a major challenge for hybrid Sn-Pb PSCs and their tandems, and thus more effective strategies must be developed to overcome these issues and drive their further development. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a perovskite cell based on indium trifluoromethanesulfonate (In(OTf)) passivated perovskite layer and a preparation method thereof. 2+ The strong coordination effect of In can delay the rapid crystallization of Sn perovskite in Sn-Pb perovskite. 3+ The redox potential (-0.34 eV) is lower than that of Sn 2+ (-0.14eV) is more negative. According to the standard reduction potential, In 3+ Sn 2+ When perovskite films or PSCs are exposed to oxygen, In 3+ Priority over Sn 2+ oxidation to protect the narrow bandgap Sn-Pb perovskite. Therefore, the triflate anion reacts with In 3+ The synergistic strengthening effect of positive ions achieves high-quality and stable tin-lead perovskite batteries.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:
[0009] A perovskite cell based on an In(OTf) passivated perovskite layer consists of a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a hole blocking layer and a metal electrode, wherein the perovskite layer also contains an In(OTf) passivator.
[0010] In some specific embodiments, the transparent conductive substrate is any one of pre-treated ITO conductive glass and FTO conductive glass.
[0011] In some specific embodiments, the hole transport layer is PEDOT:PSS (AI 4083). Preferably, the thickness of the hole transport layer is 50 to 100 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0012] In some specific embodiments, the perovskite precursor component of the perovskite layer is CsFASnPbI 3 The thickness of the perovskite layer is preferably 600-800 nm, for example, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, etc.
[0013] In some preferred embodiments, the amount of the In(OTf) passivator incorporated into the perovskite precursor is 0.1-0.3 mg / mL, for example, 0.1 mg / mL, 0.15 mg / mL, 0.2 mg / mL, 0.25 mg / mL, 0.3 mg / mL, etc.
[0014] In some specific embodiments, the electron transport layer is C60; preferably, the thickness of the electron transport layer is 10 to 40 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, etc.
[0015] In some specific embodiments, the hole blocking layer is BCP. Preferably, the hole blocking layer has a thickness of 2 to 5 nm, such as 2 nm, 3 nm, 4 nm, 5 nm, etc.
[0016] In some specific embodiments, the metal electrode is any one of Ag, Cu, and Au; preferably, the thickness of the electrode is 80 to 120 nm, for example, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, etc.
[0017] On the other hand, the aforementioned method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer comprises the following steps:
[0018] 1) Pre-treating the transparent conductive substrate;
[0019] 2) preparing a hole transport layer on a clean ITO substrate;
[0020] 3) Spin coating the perovskite precursor solution with In(OTf) passivator on the hole transport layer, and dropwise adding anti-solvent during the spin coating process, followed by annealing to obtain the perovskite layer;
[0021] 4) After cooling to room temperature, an electron transport layer, a hole blocking layer and an electrode are sequentially prepared on the perovskite layer to obtain a perovskite cell based on an In(OTf) passivated perovskite layer.
[0022] In some specific implementation schemes, the pretreatment of step 1) is: the ITO glass is cleaned with glass cleaning liquid, isopropyl alcohol and deionized water in sequence, and then blown dry with nitrogen to obtain a clean ITO conductive substrate.
[0023] In some specific embodiments, in step 2), a hole transport layer is prepared on a clean ITO substrate by spin coating;
[0024] In some preferred embodiments, the spin coating condition of the hole transport layer is 3000-4000 rpm, for example, 3500 rpm for 30s to 50s, for example, 40s, and annealing in air at a temperature of 120°C to 140°C, for example, 130°C, and an annealing time of 15min to 30min, for example, 20min, 25min, etc.
[0025] In some specific embodiments, the molar ratio of the components in the perovskite precursor solution in step 3) is CsI:FAI:SnI 2 ∶PbI 2 =0.05:0.95:0.5:0.5, the solvent is a mixed solvent of DMF and DMSO, the volume ratio is DMF:DMSO=4:1, and the anti-solvent is chlorobenzene;
[0026] Preferably, the spin coating condition of the perovskite layer is 3000-5000 rpm, for example, 3500 rpm for 60s-90s, for example, 60s, 70s, 80s, 90s, etc., and chlorobenzene is added dropwise from 20s to 30s, for example, from 25s to 80s; annealing is carried out in a glove box, and the annealing temperature is 80°C to 110°C, for example, the annealing time at 90°C or 100°C is 10-30min, for example, 15min, 20min, 25min, etc.
[0027] In some specific embodiments, in step 4), a vacuum evaporation method is used to sequentially vacuum deposit an electron transport layer, a hole blocking layer and an electrode on the perovskite layer.
[0028] In some specific embodiments, during vacuum evaporation, the vacuum degree of the chamber is not greater than 5×10 -4 Pa.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] In the perovskite cell based on the passivation perovskite layer of indium trifluoromethanesulfonate (In(OTf)), the trifluoromethanesulfonate radical and Sn 2+ The strong coordination effect of In can delay the rapid crystallization of Sn perovskite in Sn-Pb perovskite. 3+ The redox potential (-0.34 eV) is lower than that of Sn 2+(-0.14eV) is more negative. According to the standard reduction potential, In 3+ Sn 2+ When perovskite films or PSCs are exposed to oxygen, In 3+ Priority over Sn 2+ oxidation to protect the narrow bandgap Sn-Pb perovskite. Therefore, the triflate anion reacts with In 3+ The synergistic strengthening effect of positive ions achieves high-quality and stable tin-lead perovskite batteries.
[0031] The traditional method of anti-oxidation of tin-lead perovskite is usually to introduce excess Sn into the tin-lead perovskite. 2+ , but this does not fundamentally solve the problem of Sn 2+ The problem of spontaneous oxidation. The present invention uses (OTf) 3- WithIn 3+ The synergistic strengthening effect significantly delays the crystallization imbalance of tin-lead perovskite and also greatly reduces the Sn 2+ Spontaneous oxidation enables the tin-lead perovskite battery to achieve high efficiency and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the perovskite battery of the present invention.
[0033] Figure 2 This is a JV curve diagram of the perovskite battery of Example 1 of the present invention.
[0034] Figure 3 This is a JV curve diagram of the perovskite cell according to Example 2 of the present invention.
[0035] Figure 4 This is a JV curve diagram of the perovskite battery of Example 3 of the present invention.
[0036] Figure 5 This is a JV curve diagram of the perovskite cell of Example 4 of the present invention.
[0037] Figure 6 This is a JV curve diagram of the perovskite cell of Example 5 of the present invention.
[0038] Figure 7 This is a JV curve diagram of the perovskite cell of Example 6 of the present invention.
[0039] Figure 8 This is a JV curve diagram of the perovskite battery of Comparative Example 1 of the present invention.
[0040] Fig. 9 This is a comparison chart of the light stability of the perovskite cells of Comparative Example 1 and Example 4 of the present invention. DETAILED DESCRIPTION
[0041] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0042] As attached Figure 1 As shown, the perovskite cell based on the In(OTf) passivated perovskite layer of the present invention is composed of a transparent conductive substrate, a hole transport layer 3, a perovskite layer 4, an electron transport layer 5, a hole blocking layer 6 and a metal electrode 7, wherein the perovskite layer further contains an In(OTf) passivator. The transparent conductive substrate is composed of glass 1 and ITO 2.
[0043] In the present invention, the transparent conductive substrate is any one of pretreated ITO conductive glass and FTO conductive glass. The transparent conductive substrate of the present invention is a common substrate in the art, and can be etched and cleaned with reference to the prior art without special restrictions. For example, the ITO glass is cleaned with glass cleaning liquid, isopropyl alcohol and deionized water in sequence, and then blown dry with nitrogen to obtain a clean ITO conductive substrate.
[0044] Then, a hole transport layer is prepared on a clean ITO substrate, for example, by spin coating; wherein the spin coating conditions of the hole transport layer are 3000-4000 rpm for 30s to 50s, annealing in air, annealing temperature is 120°C to 140°C, and annealing time is 15min to 30min.
[0045] Then, a perovskite precursor solution containing an In(OTf) passivator is spin-coated on the hole transport layer, and an anti-solvent is added during the spin-coating process, followed by annealing to obtain a perovskite layer; wherein the molar ratio of each component in the perovskite precursor solution is CsI:FAI:SnI 2 ∶PbI 2 =0.05:0.95:0.5:0.5, the solvent is a mixed solvent of DMF and DMSO, the volume ratio is DMF:DMSO=4:1, and the anti-solvent is chlorobenzene; the spin coating conditions of the perovskite layer are 3000-5000 rpm for 60s-90s, and chlorobenzene is added dropwise for 20s-30s; annealing is performed in a glove box at a temperature of 80°C-110°C and a time of 10-30min.
[0046] Finally, after cooling to room temperature, an electron transport layer, a hole blocking layer and an electrode are prepared in sequence on the perovskite layer to obtain a perovskite cell based on an In(OTf) passivated perovskite layer.
[0047] In the present invention, the transparent conductive substrate, hole transport layer, electron transport layer, hole blocking layer and metal electrode may refer to the prior art unless otherwise specified, which is well known to those skilled in the art and will not be described in detail in the present invention.
[0048] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0049] The main raw materials used in the following examples are from the following sources:
[0050] Cesium iodide (CsI, 99.99%), formamidine iodide (FAI, 99.5%), C60 (99%), PEDOT:PSS (AI 4083) and BCP (99.5%) were purchased from Xi'an Yuriguang Energy Co., Ltd. 2 , 99.99%) was purchased from TCI; indium trifluoromethanesulfonate (In(OTf), 98%) was purchased from Aladdin; unless otherwise stated, other chemical reagents were obtained from Sigma-Aldrich. All purchased chemicals were used directly without purification.
[0051] Example 1
[0052] A method for preparing a perovskite battery, the process is as follows:
[0053] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0054] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter head, 200 μL was spin-coated on the ITO glass at 3000 rpm for 30 seconds, and then annealed at 120°C in air for 30 minutes to obtain a hole transport layer with a thickness of 100 nm.
[0055] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio DMF:DMSO=4:1, then add 0.1mg of In(OTf), after fully dissolved, filter with 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin-coat on the hole transport layer, the spin coating process is 3000rpm spin coating for 60s, and add 200μL of chlorobenzene at the countdown of 20s, and then anneal at 110℃ for 15min in the glove box to obtain a perovskite layer with a thickness of 800nm;
[0056] (4) After cooling to room temperature, 10 nm thick C60, 2 nm thick BCP, and 80 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0057] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 2 As shown, the forward scanning open circuit voltage of the battery sample is 0.897V, and the short circuit current density is 32.4mA / cm 2 , fill factor 0.79, photoelectric conversion efficiency 23.1%. Reverse scanning open circuit voltage 0.897V, short circuit current density 32.3mA / cm 2 , fill factor 0.81, photoelectric conversion efficiency 23.5%
[0058] Example 2
[0059] A method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer, the process is as follows:
[0060] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0061] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter head, 200 μL was spin-coated on the ITO glass at 3000 rpm for 30 seconds, and then annealed at 120°C in air for 30 minutes to obtain a hole transport layer with a thickness of 100 nm.
[0062] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio DMF:DMSO=4:1, then add 0.2mg of In(OTf), after fully dissolved, filter with a 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin-coat on the hole transport layer, the spin coating process is 3000rpm spin coating for 60s, and add 200μL of chlorobenzene at the countdown of 20s, and then anneal at 110℃ for 15min in a glove box to obtain a perovskite layer with a film thickness of 800nm;
[0063] (4) After cooling to room temperature, 10 nm thick C60, 2 nm thick BCP, and 80 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0064] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 3 As shown, the forward scanning open circuit voltage of the battery sample is 0.892V, and the short circuit current density is 32.4mA / cm 2 , fill factor 0.78, photoelectric conversion efficiency 22.7%. Reverse scanning open circuit voltage 0.892V, short circuit current density 32.2mA / cm 2 , fill factor 0.80, and photoelectric conversion efficiency 23.3%.
[0065] Example 3
[0066] A method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer, the process is as follows:
[0067] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0068] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter head, 200 μL was spin-coated on the ITO glass at 3000 rpm for 30 seconds, and then annealed at 120°C in air for 30 minutes to obtain a hole transport layer with a thickness of 100 nm.
[0069] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio DMF:DMSO=4:1, then add 0.3mg of In(OTf), after fully dissolved, filter with 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin-coat on the hole transport layer, the spin coating process is 3000rpm spin coating for 60s, and add 200μL of chlorobenzene at the countdown of 20s, and then anneal at 110℃ for 15min in the glove box to obtain a perovskite layer with a film thickness of 800nm;
[0070] (4) After cooling to room temperature, 10 nm thick C60, 2 nm thick BCP, and 80 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0071] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 4 As shown, the forward scanning open circuit voltage of the battery sample is 0.901V, and the short circuit current density is 32.8mA / cm 2 , fill factor 0.79, photoelectric conversion efficiency 23.5%. Reverse scanning open circuit voltage 0.901V, short circuit current density 32.7mA / cm 2 , fill factor 0.81, and photoelectric conversion efficiency 23.9%.
[0072] Example 4
[0073] A method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer, the process is as follows:
[0074] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0075] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter, 200 μL was spin-coated on the ITO glass at 4000 rpm for 50 s, and then annealed at 140 °C in air for 15 min to obtain a hole transport layer with a thickness of 50 nm.
[0076] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio DMF:DMSO=4:1, then add 0.2mg of In(OTf), after fully dissolved, filter with 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin-coat on the hole transport layer, the spin coating process is 3000rpm spin coating for 60s, and add 200μL of chlorobenzene at the countdown of 20s, and then anneal at 110℃ for 15min in the glove box to obtain a perovskite layer with a film thickness of 750nm;
[0077] (4) After cooling to room temperature, 40 nm thick C60, 5 nm thick BCP, and 120 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0078] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 5 As shown, the forward scanning open circuit voltage of the battery sample is 0.891V, and the short circuit current density is 32.4mA / cm 2 , fill factor 0.78, photoelectric conversion efficiency 22.6%. Reverse scanning open circuit voltage 0.892V, short circuit current density 32.1mA / cm 2 , fill factor 0.80, and photoelectric conversion efficiency 23.1%.
[0079] Example 5
[0080] A method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer, the process is as follows:
[0081] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0082] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter, 200 μL was spin-coated on the ITO glass at 4000 rpm for 50 s, and then annealed at 140 °C in air for 15 min to obtain a hole transport layer with a thickness of 50 nm.
[0083] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio DMF:DMSO=4:1, then add 0.2mg of In(OTf), after fully dissolved, filter with 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin-coat on the hole transport layer, the spin coating process is 5000rpm spin coating for 90s, and add 200μL of chlorobenzene at the countdown of 30s, and then anneal at 80℃ for 30min in the glove box to obtain a perovskite layer with a thickness of 700nm;
[0084] (4) After cooling to room temperature, 40 nm thick C60, 5 nm thick BCP, and 120 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0085] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 6 As shown, the forward scanning open circuit voltage of the battery sample is 0.885V, and the short circuit current density is 32.5mA / cm 2 , fill factor 0.78, photoelectric conversion efficiency 22.5%. Reverse scanning open circuit voltage 0.885V, short circuit current density 32.3mA / cm 2 , fill factor 0.80, and photoelectric conversion efficiency 23.2%.
[0086] Example 6
[0087] A method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer, the process is as follows:
[0088] (1) ITO glass cleaning: The ITO glass was cleaned with glass cleaning liquid, isopropyl alcohol and deionized water for 30 min in sequence, and then dried with nitrogen to obtain a clean ITO conductive substrate;
[0089] (2) Preparation of hole transport layer: After filtering the hole transport layer PEDOT:PSS (AI 4083) with a polytetrafluoroethylene (PTFE) filter, 200 μL was spin-coated on the ITO glass at 3500 rpm for 40 s, and then annealed at 130 °C in air for 20 min to obtain a hole transport layer with a thickness of 75 nm.
[0090] (3) Preparation of perovskite layer: Prepare 1 mL of 1.8 M Cs 0.05 FA 0.95 Sn 0.5 Pb 0.5 I 3 Precursor solution, solvent volume ratio is DMF:DMSO=4:1, then add 0.2mg of In(OTf), after fully dissolved, filter with 0.22μm PTFE filter to obtain a clear perovskite precursor solution. Take 40μL and spin coat on the hole transport layer, the spin coating process is 4000rpm spin coating for 75s, and add 200μL of chlorobenzene at the countdown of 25s, and then anneal at 100℃ for 20min in the glove box to obtain a perovskite layer with a film thickness of 720nm;
[0091] (4) After cooling to room temperature, 20 nm thick C60, 3 nm thick BCP, and 100 nm thick Ag (Ag electrode area of 0.058 cm) were vacuum-deposited on the perovskite layer. 2) (During vacuum deposition, the vacuum degree of the cavity is not greater than 5×10 -4 Pa). A complete perovskite solar cell is obtained.
[0092] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 7 As shown, the forward scanning open circuit voltage of the battery sample is 0.890V, and the short circuit current density is 32.7mA / cm 2 , fill factor 0.79, photoelectric conversion efficiency 23.1%. Reverse scanning open circuit voltage 0.890V, short circuit current density 32.5mA / cm 2 , fill factor 0.81, and photoelectric conversion efficiency 23.5%.
[0093] Comparative Example 1
[0094] The same steps and parameters as those in Example 1 are used, except that in Example 1, the process of adding In(OTf) to the precursor in step (3) is removed.
[0095] At AM 1.5, 100mW / cm 2 Under standard light intensity, such as Figure 8 As shown, the forward scanning open circuit voltage of the battery sample is 0.826V, and the short circuit current density is 32.5mA / cm 2 , fill factor 0.67, photoelectric conversion efficiency 18.1%. Reverse scanning open circuit voltage 0.827V, short circuit current density 31.4mA / cm 2 , fill factor 0.77, and photoelectric conversion efficiency 20.1%.
[0096] Combining the JV curve data of Examples 1-6 with that of Comparative Example 1, the introduction of In(OTf) into the perovskite layer significantly improves the open circuit voltage and fill factor of the battery, so the efficiency of the examples is increased by about 3-4% compared to the comparative example.
[0097] The samples prepared in Example 4 and Comparative Example 1 were subjected to stability tests. The test method is as follows:
[0098] In a nitrogen atmosphere glove box, Example 4 and Comparative Example 1 were tested for light stability under the conditions of 25°C and 1 sun of continuous lighting. Fig. 9 As shown, from the light stability data, it can be seen that after 1400 hours of illumination, the efficiency of comparative example 1 decays to less than 60% of the initial efficiency, while the efficiency of example 4 is still greater than 80% of the initial efficiency.
[0099] It can be seen from the efficiency data and stability data of the embodiments and comparative examples that by passivating the perovskite layer with indium trifluoromethanesulfonate, efficient and stable tin-lead perovskite batteries can be achieved, providing a convenient and feasible method for promoting the industrialization of perovskite batteries.
[0100] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite cell based on an In(OTf) passivated perovskite layer, comprising a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a hole blocking layer and a metal electrode, characterized in that: The perovskite layer also includes an In(OTf) passivator.
2. The perovskite battery according to claim 1, characterized in that The transparent conductive substrate is any one of pre-treated ITO conductive glass and FTO conductive glass; and / or The hole transport layer is PEDOT:PSS (AI 4083), and preferably, the thickness of the hole transport layer is 50-100 nm.
3. The perovskite battery according to claim 1, characterized in that The perovskite precursor component of the perovskite layer is CsFASnPbI3, and the thickness of the perovskite layer is preferably 600-800nm; Preferably, the amount of the In(OTf) passivator incorporated into the perovskite precursor is 0.1-0.3 mg / mL.
4. The perovskite battery according to claim 1, characterized in that The electron transport layer is C60; preferably, the thickness of the electron transport layer is 10 to 40 nm; and / or The hole blocking layer is BCP, preferably, the thickness of the hole blocking layer is 2-5 nm; and / or The metal electrode is any one of Ag, Cu and Au; preferably, the thickness of the electrode is 80-120 nm.
5. The method for preparing a perovskite cell based on an In(OTf) passivated perovskite layer according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Pre-treating the transparent conductive substrate; 2) preparing a hole transport layer on a clean ITO substrate; 3) Spin coating a perovskite precursor solution containing an In(OTf) passivating agent on the hole transport layer, and dropwise adding an anti-solvent during the spin coating process, followed by annealing to obtain a perovskite layer; 4) After cooling to room temperature, an electron transport layer, a hole blocking layer and an electrode are sequentially prepared on the perovskite layer to obtain a perovskite cell based on an In(OTf) passivated perovskite layer.
6. The preparation method according to claim 5, characterized in that: The pretreatment of step 1) is: the ITO glass is cleaned with glass cleaning liquid, isopropyl alcohol and deionized water in sequence, and then blown dry with nitrogen to obtain a clean ITO conductive substrate.
7. The preparation method according to claim 5, characterized in that: In step 2), a hole transport layer is prepared on a clean ITO substrate by spin coating; Preferably, the spin coating condition of the hole transport layer is 3000-4000 rpm for 30s to 50s, and annealing in air at a temperature of 120° C. to 140° C. for 15min to 30min.
8. The preparation method according to claim 5, characterized in that: The molar ratio of each component in the perovskite precursor solution in step 3) is CsI:FAI:SnI2:PbI2=0.05:0.95:0.5:0.5, the solvent is a mixed solvent of DMF and DMSO, the volume ratio is DMF:DMSO=4:1, and the anti-solvent is chlorobenzene; Preferably, the perovskite layer is spin-coated at 3000-5000 rpm for 60-90 s, and chlorobenzene is added dropwise 20-30 s before being annealed in a glove box at a temperature of 80° C. to 110° C. for 10-30 min.
9. The preparation method according to claim 5, characterized in that: In step 4), a vacuum evaporation method is used to sequentially vacuum deposit an electron transport layer, a hole blocking layer and an electrode on the perovskite layer.
10. The preparation method according to claim 9, characterized in that: During vacuum deposition, the vacuum degree of the chamber should not exceed 5×10 -4 Pa.
